Coats’ Disease-Related Macular Edema Treated with Combined Aflibercept and Laser Photocoagulation - Wen-Shi Shieh; Gaurav K. Shah; Kevin J. Blinder (Case Reports in Ophthalmological Medicine)
Purpose. To describe the clinical response of refractory macular edema associated with Coats’ disease following treatment with aflibercept and laser photocoagulation. Methods. Case report. Results. A 17-year-old female presented with decreased vision of the left eye. Ophthalmic exam demonstrated intraretinal hemorrhages and exudation with associated edema centrally. Angiographic evaluation revealed central leaking microaneurysms and peripheral capillary dropout. These findings and a systemic work-up that yielded an incidental Factor V Leiden mutation lead to a diagnosis of Coats’ disease. Initial treatment consisted of laser photocoagulation and intravitreal bevacizumab but with poor response. Switching to intravitreal aflibercept resulted in resolution of the refractory macular edema and improvement of visual acuity to 20/25 in the left eye. Conclusion. We describe a case of refractory macular edema which responded more favorably to intravitreal aflibercept compared with bevacizumab when combined with laser photocoagulation in a patient with Coats’ disease.